Disentangling the Range of Responses to Threats, Hazards and Disasters. Vulnerability, Resilience and Adaptation in question - Magali Reghezza-Zitt; Samuel Rufat (Cybergeo, 2019)
The succession of hazards, threats and disasters management and reduction international frameworks since the 1990s coincides with the promotion of new notions. The emergence of these notions frames the debate: are semantic evolutions modifying practices at the margin, paradigm changes or performative tools allowing practice maintenance? A retrospective view shows that these notions succeed each other as management actors encounter obstacles to yielding practical content. There are constant dialectics between the academic and operational spheres. The purpose of this article is to explain the performativity of the concepts, to identify the contradictions and to contemporize the effects of counter-productivity. The articulation of vulnerability towards resilience and then adaptation is presented as a solution to the problems posed by uncertainty and the difficulties of dealing with complexity. However, those new frameworks lead to a triple displacement of the problem, in time and space and on individuals instead of actually addressing it. These limitations and some theoretical contradictions lead to counter-productive measures. The purpose of this article is to overcome these by focusing on the notion of response. The goal is to build a median proposition between two poles: the socio-technical paradigm of vulnerability and the socio-ecological paradigm of resilience and adaptation. Vulnerability, resilience and adaptation are considered tools enabling the response’s orientation. The response then becomes operationalized into different objectives and measures. We then propose to reconstruct a response in a non-contradictory way, by taking out non-commensurable frameworks. The notion of response enables us to find a middle term between an all-encompassing framework, which retains the relevant orientations of the previous frameworks, but that is not contradictory. Responses are not a set of global solutions, large strategic plans or textbook prescriptions, but a vast project undertaken to mobilize more robust tools and understand risk as socially produced and constructed.